Icing protection system for wind turbine blade with graphene electrothermal films - Ye Tingting; Wang Tongguang; Li Hui; Chen Cheng (2016)
The invention relates to an icing protection system for a wind turbine blade with graphene electrothermal films. The graphene epoxy glass fiber laminated plate structure is adopted, a blade outer skin lapping layer is laid on the surface of a mold, and the surface of the blade outer skin lapping layer is coated with the graphene electrothermal film. The long and narrow graphene electrothermal film for continuous heating is arranged between the front edge subarea and spanwise subarea of the wind turbine blade, and the graphene electrothermal films for periodic heating are arranged at other areas. The blade lapping layer structure is laid continuously; after a blade housing is lapped completely, a vacuum auxiliary material is laid, epoxy resin is used as a resin matrix for vacuum infusing and curing molding of the blade housing, and thus the blade icing protection system can be formed. By the adoption of the system, the phenomenon that the graphene electrothermal films are exposed to the external environment to